Individual attitudes and market dynamics towards imprecision - Christoph Huber; Julia Rose (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
In real world financial markets, dividend processes as well as fundamental values are governed by imprecision; neither the objective probabilities of returns nor the actual amounts of possible returns are known for certain. With a novel experimental approach, we analyze the impact of risk, imprecision in probabilities (ambiguity), imprecision in outcomes, and a combination of the latter two in an individual decision task and in a market environment. In contrast to the previous literature, we do not find any significant imprecision premia for imprecise probabilities. However, we do find significant and persistent imprecision-in-outcomes seeking in the individual task as well as the market setting. Looking deeper into the combination of individual attitudes and market behavior, we find that these patterns survive despite a high level of heterogeneity in individual's beliefs about outcomes.
Keywords: G11; G12; C92; D81; 330; ambiguity aversion; imprecision; uncertainty; asset markets; experimental finance